2006
DOI: 10.1021/jf062276h
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of Tea Compounds against Human Cancer Cells

Abstract: The content of the biologically active amino acid theanine in 15 commercial black, green, specialty, and herbal tea leaves was determined as the 2,4-dinitrophenyltheanine derivative (DNP-theanine) by a validated HPLC method. To define relative anticarcinogenic potencies of tea compounds and teas, nine green tea catechins, three black tea theaflavins, and theanine as well as aqueous and 80% ethanol/water extracts of the same tea leaves were evaluated for their ability to induce cell death in human cancer and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 52 publications
4
112
0
Order By: Relevance
“…The results indicated that the glycoalkaloids with chacotriose exhibited greater suppression than the glycoalkaloids with solatriose against Plasmodium yoelii in mice. Our results were similar to those previously reported for the glycoalkaloids chaconine and solanine in disrupting cell membranes (Keukens et al, 1995(Keukens et al, , 1996, antifungal activity (Fewell & Roddick, 1993), blocking of sodium ion active transport in frog skin (Blankemeyer et al, 1995), antitumorigenic activity (Lee et al, 2004;Friedman et al, 2005) and Xenopus embryo teratogenesis (Friedman et al, 1992;Rayburn et al, 1994). As mentioned above, the correlation of solamargine and solasonine in antimalarial activities was similar to that in antifungal activity (Cipollini & Levey, 1997), developmental toxicology in frog embryos (Blankemeyer et al, 1998) and antiproliferative activities against human colon and liver cancer cell lines (Lee et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results indicated that the glycoalkaloids with chacotriose exhibited greater suppression than the glycoalkaloids with solatriose against Plasmodium yoelii in mice. Our results were similar to those previously reported for the glycoalkaloids chaconine and solanine in disrupting cell membranes (Keukens et al, 1995(Keukens et al, , 1996, antifungal activity (Fewell & Roddick, 1993), blocking of sodium ion active transport in frog skin (Blankemeyer et al, 1995), antitumorigenic activity (Lee et al, 2004;Friedman et al, 2005) and Xenopus embryo teratogenesis (Friedman et al, 1992;Rayburn et al, 1994). As mentioned above, the correlation of solamargine and solasonine in antimalarial activities was similar to that in antifungal activity (Cipollini & Levey, 1997), developmental toxicology in frog embryos (Blankemeyer et al, 1998) and antiproliferative activities against human colon and liver cancer cell lines (Lee et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have suggested that the paired glycoalkaloids might act synergistically in plant defense. Positive synergistic effects have been observed for chaconine and solanine in permeation of liposomes (Roddick & Rijnenberg, 1986), disrupting membranes (Keukens et al, 1995), antifungal (Fewell & Roddick, 1993) and antitumorigenic effects (Friedman et al, 2005). However, combinations of chaconine and solanine were slightly antagonistic or non-interactive in acetylcholinesterase inhibition (Roddick, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous results confirmed that theanine inhibited the invasion of rat hepatoma cells in vitro and ex vivo (Zhang et al 2001) and hepatoma growth in vivo (Zhang et al 2002) although theanine did not show an inhibitory effect on the proliferation of rat hepatoma AH109A cells in vitro. There have been studies reporting that theanine suppressed the growth in hepatoma, prostate cancer, and colon cancer cells (Friedman et al 2007). Our results confirm for the first time the anticancer activity of theanine against growth of human lung cancer and leukemia cells as well as migration and invasion of human lung cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the isolated compounds of the ethyl acetate fraction of R. heckeliana such as ellagic acid (ED 50 value: 30.26 ± 0.77 µg/mL), caffeic acid (ED 50 value: 32.70 ± 1.65 µg/mL), and isolated catechin (ED 50 value: 35.80 ± 2.19 µg/mL) were quite effective on the estrogen receptorsensitive MCF-7 cells. Friedman et al (2007) reported that catechin was effective on MCF-7 breast cancer cells. Cytotoxicity tests were achieved by the application of the MTT assay and using catechin concentrations ranging from 50 to 400 µg/ mL.…”
Section: Application To Estrogen Receptor-sensitive Breast Cancer Celmentioning
confidence: 99%